Empirical analysis of green finance and high-quality economic development in the Yangtze River Delta based on VAR and coupling coordination model - Su Zhang; Bei-Bei Liang; Shan-Zhi Xu; Jin-Long Hou (Frontiers in Environmental Science, 2023)
The Yangtze River Delta region is one of the most active regions in China’s economic development and financial innovation, and its green finance is at the leading level in the country. To promote the integrated development of green finance in China’s Yangtze River Delta and boost high-quality economic development, this paper uses the data of three provinces and one city in the Yangtze River Delta from 2010 to 2021, constructs the green finance development index and the high-quality economic development index by entropy weight method, and constructs the VAR model to analyze the interaction between the two. The coupling coordination model is used to analyze the coupling coordination degree between green finance and high-quality economic development, and the correlation between green finance and high-quality economic development is deeply analyzed by using the gray correlation method. Finally, the gray prediction model is used to predict the coupling coordination between green finance and high-quality economic development. The research shows that green finance and high-quality economic development have short-term mutual promotion effects, and the coupling and coordination are good, but there are regional differences. The overall degree of correlation between the two is medium to upper, and the interaction force is strong. From the forecast results, the coupling coordination and coupling priority of the Yangtze River Delta region show positive development, and Anhui Province has more room for improvement. Based on the above research, this paper proposes to establish a green finance integrated development mechanism to promote regional green finance synergistic development, promote green finance infrastructure interconnection to better realize resource allocation and information sharing, attract more professionals to participate in green finance innovation, and build a favorable external development environment for green finance.